The possible “calming effect” of subchronic supplementation of a standardised phospholipid carrier-based Melissa officinalis L. extract in healthy adults with emotional distress and poor sleep conditions: results from a prospective, randomised, double-blinded, placebo-controlled clinical trial - Bano, Aasiya; Hepsomali, Piril; Rabbani, Fazle; Farooq, Umer; Kanwal, Ayesha; Saleem, Aisha; Bugti, Ali Akbar; Khan, Aftab Alam; Khalid, Zainab; Bugti, Mahroo; Mureed, Shah; Khan, Saeed; et al. (Frontiers in Pharmacology, 2023)
Background: Emotional distress conditions such as depression, anxiety, stress, and poor sleep are widespread health problems that have a significant impact on people’s lives. Conventional drugs are commonly prescribed to treat emotional distress and poor sleep conditions; however, these medications have several limitations and have shown multiple side effects. Over recent years botanicals-based pharmacological agents have gained increasing research and clinical interest in the management of emotional distress and sleep disorder. Of note, Melissa officinalis L. (MO) leaf extract has demonstrated considerable neuropharmacological properties both in animal and human studies and has emerged as a promising natural “calming agent.” However, research in this area is limited, and more studies are needed to validate its efficacy in amelioration of emotional distress and poor sleep conditions. Objectives: We aimed to assess the pharmacological effects of subchronic supplementation of an innovative standardised phospholipid carrier-based MO aqueous extract on emotional distress and poor sleep conditions. Design: A 3-week prospective, randomised, placebo-controlled, parallel-group, double-blinded clinical trial was conducted in 100 healthy adults complaining of a moderate degree of depression, anxiety, or stress, with scores of ≥14, ≥10, and ≥19, respectively, in the self-report Depression, Anxiety, and Stress Scale (DASS-42) or poor sleep, as indicated by the score of >5 in the Pittsburgh Sleep Quality Index (PSQI) scale. In addition, the impact of emotional distress and/or poor sleep on participants’ mental wellbeing, emotional feelings, and quality of life was also assessed using the self-reported Warwick–Edinburgh Mental Wellbeing Scale (WEMWBS), Positive and Negative Affect Schedule (PANAS) scale, and quality of life (WHO-QoL-BREF) scale, respectively. Results: Oral supplementation of 200 mg of phospholipid-based MO aqueous extract (Relissa™) tablets twice a day (i.e., 400 mg/day) for 3 weeks led to significant improvements in the depressive mood, anxiety, stress, positive and negative affect (emotional feelings), overall mental wellbeing, and quality-of-life scores (all p values <0.001). Supplementation of MO extract was well tolerated, and no treatment-emergent effects or serious adverse events were reported. Conclusion: According to the results of this study, the phospholipid carrier-based MO aqueous extract possesses considerable neuropharmacological properties, and its supplementation may provide a promising therapeutic option for the management of moderate emotional distress and/or poor sleep conditions. Clinical Trial Registration:clinicaltrials.gov, identifier NCT05602688.